HEGEMONY BY ANTONIO GRAMSCI IN THE LION KING FILM - Jelita Dewanty Hendarsyah; Abd. Hannan EF; Lili Awaludin (Universitas Islam Negeri Sunan Gunung Djati, 2021)
In this thesis, the researcher focuses on discussing the coup in The Lion King film directed by John Favreau in 2019. This research is based on the model proposed by Antonio Gramsci's hegemony of power, this theory covers the causes of the normal practice of overthrowing power and the relationship of consent using the power structure. The purpose of this research is to find out and understand the relationship between the conflict between the main characters causing the coup d'etat represented in film literature; especially in examining the similarities in the causes of the coup d'etat from the perspective of the Hegemony of Power, the three aspects that caused the coup d'etat; Obsession, Discrimination, and Betrayal. To find out the truth, the researcher focuses on examining the hegemony of power that is applied in The Lion King Film. Hegemony is applied in the form of driving bad opinions to achieve the desired result, namely becoming a king. The results of this study indicate that there are 3 reasons for the application of the hegemony of power contained in The Lion King Film, obsession, driving bad opinion, cunning.Keywords : Coup, research, The Lion King film, overthrowing of power, government.